MNGI-40. MENINGIOMA RESECTION SURGERY IN ELDERLY PATIENTS: AN ANALYSIS OF A NATIONAL DATABASE. (5th November 2018) - Lobbous, Mina; Gupta, Sahil; Shapshak, Angela
Abstract: OBJECTIVE: Meningiomas are often benign and mostly asymptomatic, and the treatment approaches may include open surgical resection, radiosurgery, and/or watchful waiting. Reported morbidity and mortality rates for elderly patients undergoing meningioma resection vary widely. We sought to investigate mortality rates for elderly patients undergoing craniotomy for meningioma resection using the Nationwide Inpatient Sample. METHODS: The Nationwide Inpatient Sample (NIS) datasets from 2003 to 2013 were used to identify patient admissions for meningioma resection based on the ICD-9-CM code 01.51. Age categories were defined as 70 years of age. Primary outcomes were in-hospital mortality, poor outcomes (defined as death or discharge to a facility other than home), cost and length of hospitalization. RESULTS: A total of 24, 953 patients were identified who underwent meningioma resection during 2003–2013 of which 20.4% were elderly (>70 years). Each of the primary outcomes was heavily influenced by the advancing age. In-patient mortality was higher in the elderly as compared to the younger patients (3.5% vs 1%), as was the rate of a poor outcome (64.8% vs 28.1%). Elderly patients also had a higher cost ($104425 vs $96012) and length of hospitalization (8.9 vs 6.8 days). CONCLUSION: In our study, age > 70 was strongly associated with adverse outcomes after meningioma resection. This increased risk should be taken into account when considering surgical intervention in this subgroup; closer perioperative monitoring may be warranted.